Sinonasal Lymphoma: A Rare Pathology Presenting with Common Post-Influenza Symptoms - Sobani, Muhamad Ariff; Mohamad Fuzi, Noor Shahira; Kamarudin, Intan Kartika; Rahim, Norazila Abdul; Nik Hussin, Nik Mohd Hazleigh (International Journal of Human and Health Sciences (IJHHS), 2023)
Sinonasal malignancies are uncommon and only account for 3% of head and neck cancers. Despite diffuse large B-cell lymphomas (DLBCL) being the most common type of non-Hodgkins lymphoma occurring at various extranodal sites, its occurrence as a sinonasal tumor is exceedingly rare. Early detection and treatment of sinonasal lymphoma, have favourable outcomes with improvements in the 2-year and 5-year survival rates. We are reporting a case of primary sinonasal DLBCL in a 63-year-old lady who initially presented with nasal obstruction and epistaxis, both common symptoms in patients who have had a recent Influenza A infection. However, due to the unilaterality and progressive nature of her nasal obstruction, she warranted a specialist otorhinolaryngology assessment. Naso endoscopy revealed a unilateral nasal mass extending from the right middle meatus to the nasal floor and was friable with contact bleeding. These clinical findings are similarly seen in most of the various types of sinonasal malignancies, and diagnosis can be challenging. Pathologists rely upon immunohistochemical staining profiles to differentiate this highly heterogeneous group of malignancies. Histopathological examination confirmed the diagnosis of sinonasal lymphoma. The treatment of this rare pathological entity is discussed. International Journal of Human and Health Sciences Supplementary Issue: 2023 Page: S28